354 RENAL RESPONSES TO ANGIOTENSIN II IN MICE LACKING THE GENE FOR TUMOR NECROSIS FACTOR-α. Issue 1 (1st January 2007) - Kopkan, L.; Castillo, A.; Francis, J.; Majid, D. S.A.
Abstract : Recent studies have implicated a role for a proinflammatory cytokine, tumor necrosis factor-α (TNF-α), in angiotensin II (ANGII)-induced renal injury and the development of salt-sensitive hypertension. To examine this relationship between TNF-α and ANGII actions in the kidney, we assessed renal responses to acute ANG II (1 ng/min/g for 30 minutes, IV) in anesthetized knockout (KO) mice lacking TNF-α and compared these responses with those of wild-type (WT) mice. Systemic blood pressure (BP) was recorded from a cannula placed in the left carotid artery. Renal blood flow (RBF) and glomerular filtration rate (GFR) were measured by PAH and inulin clearances, respectively. Compared with WT ( n = 6), KO ( n = 8) mice did not have significant differences in the basal values of BP (92 ± 4 and 99 ± 2 mm Hg), RBF (3.8 ± 0.3 and 3.4 ± 0.2 mL.min −1 .g −1 ), GFR (0.74 ± 0.04 and 0.75 ± 0.03 mL.min −1 .g −1 ), urine flow (V, 8.8 ± 0.4 and 9.9 ± 0.6 μL.min −1 .g −1 ), and sodium excretion (UNa V, 0.87 ± 0.07 and 0.93 ± 0.12 μmol.min −1 .g −1 ). However, KO exhibit lower urinary nitrite/nitrate (UNOx V; 0.13 ± 0.02 vs 0.35 ± 0.07 nmol.min −1 .g −1 ) and 8-isoprostane excretion (UISO V; 1.26 ± 0.05 vs 1.97 ± 0.20 pg.min −1 .g −1 ) compared with WT. ANGII caused similar increment in BP in both KO and WT (Δ24 ± 3 and Δ26 ± 2 mm Hg). Interestingly, ANGII caused minimal decrease in RBF (−3 ± 2%) in KO compared with WT (−30 ± 5%). Moreover, ANGII increased GFR in KO (7 [138} 2%) but not in WT. Although V and UNa V responses to ANGII were not much different between the the strains, there were lower UNOx V (92 ± 19% vs 143 [138} 52%; p < .05) as well as UISO V (87 ± 8% vs 116 ± 14%; p < .05) responses to ANGII in KO compared with WT mice. These data indicate that TNF-α is involved in the changes in renal hemodynamics as well as nitrosative and oxidative stress mechanisms induced by ANGII.